Nano-additive manufacturing of multilevel strengthened aluminum matrix composites. (1st March 2023) - Shao, Chenwei; Li, Haoyang; Zhu, Yankun; Li, Peng; Yu, Haoyang; Zhang, Zhefeng; Gleiter, Herbert; McDonald, André; Hogan, James
Abstract: Nanostructured materials are being actively developed, while it remains an open question how to rapidly scale them up to bulk engineering materials for broad industrial applications. This study propose an industrial approach to rapidly fabricate high-strength large-size nanostructured metal matrix composites and attempts to investigate and optimize the deposition process and strengthening mechanism. Here, advanced nanocrystalline aluminum matrix composites (nanoAMCs) were assembled for the first time by a novel nano-additive manufacturing method that was guided by numerical simulations (i.e. the in-flight particle model and the porefree deposition model). The present nanoAMC with a mean grain size <50 nm in matrix exhibited hardness eight times higher than the bulk aluminum and shows the highest hardness among all Al–Al2 O3 composites reported to date in the literature, which are the outcome of controlling multiscale strengthening mechanisms from tailoring solution atoms, dislocations, grain boundaries, precipitates, and externally introduced reinforcing particles. The present high-throughput strategy and method can be extended to design and architect advanced coatings or bulk materials in a highly efficient (synthesizing a nanostructured bulk with dimensions of 50 × 20 × 4 mm 3 in 9 min) and highly flexible (regulating the gradient microstructures in bulk) way, which is conducive to industrial production and application. Highlights: A novel method for high-throughput synthesis of bulk nanocrystalline metals or MMCs was developed. Multi-level strengthened nanoAMCs with a mean grain size of <50 nm in matrix were designed and architected for the first time. The low-temperature deposition processes (parameters) were investigated and optimized by numerical simulations. Present composite with smallest matrix grains shows highest hardness among all Al–Al2 O3 composites reported in literature.